A Methodology to Control Walking Speed of Robotic Gait Rehabilitation System using Feasibility-Guaranteed Trajectories - Jung, Chan-yul; Choi, Junho; Park, Shinsuk; Kim, Seung-Jong (2015 IEEE/RSJ INTERNATIONAL CONFERENCE ON INTELLIGENT ROBOTS AND SYSTEMS (IROS), 2015)
This paper presents a novel methodology to control walking speed of an exoskeleton for gait rehabilitation of stroke patients using feasibility-guaranteed trajectories. The controller uses interaction forces to estimate the desired walking speed. Instead of allowing each joint to move around a nominal trajectory, which could lead to infeasible gait patterns, the control algorithm proposed in this paper chooses joint trajectories for desired walking speed, which generates feasible gait patterns. With the interaction forces measured during walking, the walking speed intended by the patient is estimated. Then, based on the estimated walking speed, a reference trajectory stored in a database, which is checked if kinematic constraints required for walking are met, is chosen. Since checking feasibility is performed off-line before the training sessions, it is possible to ensure stability of walking without causing any computational time on-line.